COPING WITH WORK-RELATED STRESS AMONG MARKET WORKERS. WITH SPECIAL REFERENCE TO PAVOORCHATRAM KAMARAJAR DAILY MARKET IN TENKASI DISTRICT. (International Journal of Food and Nutritional Sciences, 2022)
Man has been using many objects for his own need since the dawn of time. To put it more clearly, there are various types of foods that are consumed daily for human survival, of which vegetable is the inevitable one. In this study, the number of respondents is that the population of vegetables market workers of Tenkasi region of TamilNadu state. Primary information was collected with the help of structured questionnaire. Applied math techniques like chi-square analysis and hypothesis testing.